Compound dark tea ameliorates obesity and hepatic steatosis and modulates the gut microbiota in mice - Qu, Jianyu; Ye, Mengke; Wen, Chi; Cheng, Xianyu; Zou, Lirui; Li, Mengyao; Liu, Xiangyan; Liu, Zhonghua; Wen, Lixin; Wang, Ji (Frontiers in Nutrition, 2023)
Dark tea is a fermented tea that plays a role in regulating the homeostasis of intestinal microorganisms. Previous studies have found that dark tea can improve obesity and has a lipid-lowering effect. In this study, green tea, Ilex latifolia Thunb (kuding tea) and Momordica grosvenori (Luo Han Guo) were added to a new compound dark tea (CDT), to improve the taste and health of this beverage. High-fat diet-fed C57BL/6J mice were treated with low- (6 mg/mL) or high- (12 mg/mL) concentrations of CDT for 18 weeks to assess their effect on lipid metabolism. Our results suggest that low- and high-concentrations of CDT could reduce body weight by 15 and 16% and by 44 and 38% of body fat, respectively, by attenuating body weight gain and fat accumulation, improving glucose tolerance, alleviating metabolic endotoxemia, and regulating the mRNA expression levels of lipid metabolism-related genes. In addition, low concentrations of CDT were able to reduce the abundance of Desulfovibrio, which is positively associated with obesity, and increase the abundance of Ruminococcus, which are negatively associated with obesity. This study demonstrates the effect of CDT on ameliorating lipid metabolism and provides new insights into the research and development of functional tea beverages.